Stability of Doxycycline Absorbed on Root Canal Dentin After Obturation with Gutta-Percha/AH26 and Resilon/RealSeal at Different Time Intervals. - Behnam Bolhari; Naghmeh Meraji; Ali Nosrat; Shokoufeh Hassani (Tehran University of Medical Sciences, 2013)
Eradication of microorganisms present in the root canal system is paramount for the successful outcome of root canal therapy. The purpose of this study was to compare the of doxycycline absorbed from MTAD into root canal dentin after obturation with gutta-percha/AH26 and Resilon/RealSeal at different time intervals.Fifty-one extracted human teeth were instrumented. Thirty samples were obturated with either gutta-percha/AH26 or Resilon/self-etch RealSeal after final irrigation with MTAD. Fifteen samples were kept unobturated (positive control); six samples were obturated with either gutta-percha/AH26 or Resilon/self-etch RealSeal without MTAD irrigation (negative control). After aging for 1, 3 or 6 weeks, dentin debri were collected, the Doxycycline compound was extracted and its amount was quantified using high performance liquid chromatography. The statistical significance of the change in Doxycycline concentrations was tested with two-way ANOVA.The mean concentration of Doxycycline in dentin for one, three and six-week guttapercha/AH26 samples was 1.8±0.36, 1.22±0.22 and 0.67±0.11 respectively, whereas these concentrations in Resilon/RealSeal samples were 1.60±0.26, 0.80±0.14 and 0.59±0.01 respectively. Regarding the positive control group, these concentrations were 2.09±0.11, 1.54±0.12 and 0.72±0.07 respectively for 1, 3 and 6-week intervals. No Doxycycline was detected in negative control groups. The Doxycycline concentrations showed a significant difference forobturating materials (p=0.008). These concentrations were higher in the gutta-percha/AH26 samples than Resilon/RealSeal samples in each time interval.The remaining amount of Doxycycline bonded to dentin was higher when root canals were obturated with gutta-percha/AH26 compared to Resilon/RealSeal. The stability of Doxycycline showed a time dependent decrease.